2020
DOI: 10.1002/tea.21643
|View full text |Cite
|
Sign up to set email alerts
|

Students' attitudes toward science and science achievement: An analysis of the differential effects of science instructional practices

Abstract: The purpose of this study was to examine the predictive effects of inquiry‐based and teacher‐directed instructional practices on students' attitudes toward science and science achievement in a nationally representative sample of 7,708 15‐year‐old‐students from Taiwan who took part in the sixth cycle of the Program for International Student Assessment (PISA). The results of structural equation modeling analyses, after accounting for student demographic and socioeconomic characteristics, revealed that teacher‐di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 74 publications
(131 reference statements)
4
38
2
7
Order By: Relevance
“…It has been found in the studies that students who have inquiry based learning have higher academic achievement compared to students using other teaching methods (Chang & Mao, 1999;Jiun, Kamarudin, Talib & Hassan, 2018;Tezel, Semiz & Uçar, 2020). Unlike this result, Liou (2021) revealed that inquiry based learning practices had a significant negative effect on students' science achievement, whereas teacher directed instruction had a significant positive effect on students' science achievement. Nevertheless, as a result of many studies, it is stated that inquiry-based learning is effective on students' science achievement.…”
Section: Conclusion and Discussioncontrasting
confidence: 81%
“…It has been found in the studies that students who have inquiry based learning have higher academic achievement compared to students using other teaching methods (Chang & Mao, 1999;Jiun, Kamarudin, Talib & Hassan, 2018;Tezel, Semiz & Uçar, 2020). Unlike this result, Liou (2021) revealed that inquiry based learning practices had a significant negative effect on students' science achievement, whereas teacher directed instruction had a significant positive effect on students' science achievement. Nevertheless, as a result of many studies, it is stated that inquiry-based learning is effective on students' science achievement.…”
Section: Conclusion and Discussioncontrasting
confidence: 81%
“…Therefore, it seems that structured inquiry enabled learners to exercise control and gain a sense of ownership of the learning experience. However, this was not the case for the remaining attitudinal dimensions where less guidance was not associated with more positive attitudes (Liou, 2021).…”
Section: Discussionmentioning
confidence: 86%
“…However, as they represent a distinct trait of attitudes toward school science, they can not be grouped into a single overall score. Likewise, since research consistently found differences between girls' and boys' attitudes, gender should be considered when analyzing the impact of educational interventions (Liou, 2021). Therefore, data were analyzed using a 2 (gender) × 3 (pedagogical condition) multivariate analysis of variance (MANOVA).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports on inquiry effectiveness, however, have suggested a nonlinear relationship between inquiry-based teaching and achievement in science based on PISA (Cairns & Areepattamannill, 2019;Liou, 2020) and TIMSS data (Teig, Scherer, & Nilsen, 2018). The relationship between attitudes towards science and achievement shows moderate or weak positive relationship between variables (Liou, 2020;Osborne et al, 2003;Savelsbergh et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 98%